Dynamics of immune status indicators in patients with relapsing-remitting multiple sclerosis before and after treatment of Betfer-1a drug - Vdovichenko, N; Kolyada, T; Tupotilov, O; Negreba, T.; Kolyada, O. (Annals of Mechnikov’s Institute, 2019)
The article presents the results of examination of 58 patients with relapsing-remitting multiple sclerosis (RRMS) treated IFN-β. Depending on the effectiveness of treatment, patients were divided into two groups: responders, included 37 persons (64%), in this group patients did not relapse during the year from the beginning of treatment, the degree of EDSS remained unchanged or decreased, the group EDSS before the start of therapy was 2.2 ± 1.4 points. After therapy, EDSS was 2.1 ± 1.4 points.- non-responders, this group included 21 individuals, the patient was included in the group if he had at least one relapse during the year and / or an increase in the degree of disability on the EDSS was found to be 1 point or more. The group EDSS before the start of therapy was 2.5 ± 1.5 points. After therapy, EDSS was 3.0 ± 1.5 points. The immunological characteristics of the patients are presented, depending on the clinical efficacy of the treatment; the presence of disease-associated polymorphic variants of HLA-DR has been determined. After the course of therapy with IFN-β, in patients with RRMS, regardless of the clinical efficacy of treatment, the relative number of T-lymphocytes and natural killer cells remained significantly reduced. In the group of responders levels of circulating immune complexes and IgG levels did not differ from control after treatment, in contrast to the levels of lymphocytotoxic autoantibodies and complement activity, which remained elevated relative to the control. After treatment in patients with low efficacy of IFN-β therapy (nonresponders), the relative number of CD19+ cells, as well as the levels of IgG, circulating immune complexes and lymphocytotoxic autoantibodies remained elevated relative to the control group. The presence of the haplotype HLA-DRB1*1501-DQB1*0602 (one of its specific markers is allele G SNP rs9271366) is established to determine the association between the disease-associated polymorphism of HLA-DR and the effectiveness of IFN-β therapy. The presence of the minor disease-associated G allele was determined in 11 responders (29.7%) (heterozygous), another 26 patients (70.3%) were homozygous for major allele A. In the group of non-responders, 9 persons (42, 9%) were heterozygous, 12 (57.1%) were homozygous for major allele A.